Low-Dose Piperlongumine Rescues Impaired Function of Endothelial Progenitor Cells and Reduces Cerebral Ischemic Injury in High-Fat Diet-Fed Mice - Dong, Xiao-Hui; Peng, Cheng; Zhang, Yu-Yi; Jiang, Yu; Yang, Li-Jun; He, Jia-Bei; Tao, Xia; Zhang, Chuan; Chen, Alex F; Xie, He-Hui (Frontiers in Pharmacology, 2021)
It is of great clinical significance to develop potential novel strategies to prevent cardio-cerebrovascular complications in patients with hyperlipidemia. Vascular Endothelial integrity and function play a key role in the prevention of cardio-cerebrovascular diseases. Endothelial progenitor cells (EPCs) can home to sites of ischemic injury and promote endothelial regeneration and neovascularization. Hypercholesterolemia impairs the function of EPC. The present study attempted to identify the effect of piperlongumine on EPCs’ angiogenic potential and cerebral ischemic injury in high-fat diet-fed (HFD-fed) mice. Here, we showed that treatment with low-does piperlongumine (0.25mg/kg/day) for 8 weeks significantly improved EPCs function and reduced the cerebral ischemic injury (both infarct volumes and neurobehavioral outcomes) in HFD-fed mice. In addition, low-dose piperlongumine administration increased intracellular NO level and reduced intracellular O2.- level in EPCs of HFD-fed mice. Moreover, incubation with piperlongumine (1.0 μM, 24h) reduced thrombospondin-1/2 (TSP-1/2, a potent angiogenesis inhibitor) expression levels in EPCs from HFD-fed mice, increased the therapeutic effect of EPC from HFD-fed mice on cerebral ischemic injury reduction and angiogenesis promotion in HFD-fed mice, and the donor derived EPCs homed to the recipient ischemic brain. In conclusion, low-dose piperlongumine can enhance EPCs’ angiogenic potential and protect against cerebral ischemic injury in HFD-fed mice. It is implied that treatment with low-dose piperlongumine might be a potential option to prevent ischemic diseases (including stroke) in patients with hyperlipidemia, and priming with piperlongumine might be a feasible way to improve the efficacy of EPC-based therapy for ischemic diseases.